Female adolescent athletes' attitudes and perspectives on injury prevention programs. Issue 2 (February 2017) - Martinez, Jessica C.; Mazerolle, Stephanie M.; Denegar, Craig R.; Joseph, Michael F.; Pagnotta, Kelly D.; Trojian, Thomas H.; DiStefano, Lindsay J.
Abstract: Objectives: To examine what factors influence a high school female athlete's stated willingness to perform a lower extremity injury prevention program (IPP). A secondary aim was to examine if a participant's stated willingness affected her compliance with an IPP. Design: Repeated measures. Methods: We surveyed high school female field hockey, soccer and volleyball athletes before and after a season-long IPP warm-up intervention. Participants completed the Injury Prevention Program Attitude Survey (IPPAS), a paper and pencil survey utilizing Likert-style and open-ended questions. It was used to assess the athletes' willingness to perform an IPP if the data proved the player would experience improved performance, fewer injuries and risk factors, what outside factors influence their willingness to perform an IPP, who they would feel comfortable leading their team in an IPP, and what they believe an IPP can improve. Results: Participants responded that they were willing to perform an IPP if data proved that they would have fewer injury risk factors ( p  ≤ 0.001) and be less likely to suffer an ACL injury ( p  < 0.001). Improved sport performance did not play a role in participants' willingness to perform an IPP. Before and after the warm-up intervention, participants stated that stretching, strengthening, and cardiovascular activity should be included in an IPP. Participants' stated willingness and beliefs prior to the intervention did not appear to affect their compliance. Conclusions: Female adolescent athletes are willing to perform IPPs if data indicated that they would have fewer injury risk factors and suffer fewer ACL and leg injuries.